2020
DOI: 10.1016/s2215-0366(20)30046-8
|View full text |Cite
|
Sign up to set email alerts
|

Timely mental health care for the 2019 novel coronavirus outbreak is urgently needed

Abstract: The aim of this study was to investigate the impact of the COVID-19 pandemic on the attitudes towards the lifting of con nement. Methods: The data were collected using a questionnaire applied to 344 people in different regions of Algeria from April 21, 2020, for two weeks afterward, in order to determine the attitudes of the Algerian people towards the post-coronavirus COVID-19 phase. Results: The results of this study indicate that 94.2% of respondents insist on lifting the con nement to apply gradually and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

71
2,764
6
287

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 3,156 publications
(3,316 citation statements)
references
References 4 publications
71
2,764
6
287
Order By: Relevance
“…Maintaining staff mental health is essential to better control infectious diseases, although the best approach to this during the epidemic season remains unclear. 4,5 The learning from these psychological interventions is expected to help the Chinese government and other parts of the world to better respond to future unexpected infectious disease outbreaks.…”
mentioning
confidence: 99%
“…Maintaining staff mental health is essential to better control infectious diseases, although the best approach to this during the epidemic season remains unclear. 4,5 The learning from these psychological interventions is expected to help the Chinese government and other parts of the world to better respond to future unexpected infectious disease outbreaks.…”
mentioning
confidence: 99%
“…Panic is inevitable among patients and medical staff and timely mental health care for dealing with the novel coronavirus outbreak is urgently needed [8]. At present, it has been reported that many local hospital workers in Wuhan, especially nurses, have been confronting occupational exhaustion.…”
Section: Possible Coping Strategiesmentioning
confidence: 99%
“…Les patients sortis de l'hôpital Ce travail d'éducation à la santé est non seulement une contribution utile en termes de santé publique, mais il est psychiquement rassurant pour les patients et leurs proches. L'intégration de la composante altruiste du confinement est susceptible de favoriser son acceptation et son respect (51,52).…”
Section: Vulnérabilité De L'organisation Des Soins Psychiatriques à Lunclassified